Cognitive challenges in persons with spina bifida: Bearing on urological dysfunctions?. Issue 8 (22nd September 2020) - Ehrén, Ingrid; Hagman, Göran; Lindbo, Lena; Gabrielsson, Hanna; Bendt, Martina; Seiger, Åke
Abstract: Aim: To evaluate if adult persons with spina bifida (SB) who have urinary tract complications have cognitive difficulties that can be identified by neuropsychological tests. Methods: All individuals with SB ≥ 18 years of age registered at a regional outpatient clinic ( n = 219) were invited, of which, 154 persons were included. Neuropsychological assessment of their cognitive status was performed with Wechsler Adult Intelligence Scale®—Fourth Edition: Coding, Block design, Arithmetic's, FAS (word generation), Rey Auditory Verbal Test for learning, and delayed recall 30 min. Bladder and bowel function were assessed with questions used by the Nordic Spinal Cord Injury Registry (NSCIR) in structured interviews, by questionnaires, and by chart reviews. Results: Average neuropsychological test results for this SB population was shown to be approximately 1 SD under the median for the general population. The Coding test showed significantly lower test results as compared with the whole SB group in persons with urinary tract complications, especially urinary tract infections, reduced kidney function, dependent emptying of the bladder, and the bowel and accidental bowel leakage. The Arithmetic's test showed a significant difference between subgroups in all parameters except reduced kidney function whereas the other neuropsychological tests were significantly correlated with some but not all urological parameters. Conclusion: We propose neuropsychological testing with primarily two tests to find those persons with SB who, due to cognitive challenges, might need extra support to minimize urological complications.